The Use of L1 in Teaching English - Hermini Hermini (Institut Agama Islam Negeri Palopo, 2019)
This research aims at finding the functions of the use of L1 in teaching English. It is descriptive research. Purposive sampling technique was used to choose the sample. There were two samples in this research. The researcher used tape recorder to collect the data. It is found that the core functions of the use L1 is higher than the social function of the use L1. The core functions are record keeping; language analysis; presenting the rules of grammar, phonology, morphology, and grammar; checking comprehension; translating L1; explaining new vocabulary or material; brain storming; eliciting; testing; highlight the recent item of material and checking for sense of the students’ language and social functions are classroom management; instruction or prompts; giving advice, asking the students’ conditions; checking attendance; joking; and threaten the students to maintain discipline. As long as the lecturers or teacher use L1 appropriately it can support the teaching process.